MENUMBUHKAN PRILAKU KEWIRAUSAHAAN SANTRI MELALUI IMPLEMENTASI PENDIDIKAN BIMBINGAN KARIR (Studi Pondok Pesantren Entrepreneur Ad-Dhuha Yogyakarta) - Aisyah Khumairo (AT-TAJDID, 2018)
This research is motivated by: first. the phenomenon that occurs with increasing economic growth is not balanced with the level of income of the population. Second, the emergence of various school educational institutions and boarding schools, so that entrepreneurs as one of the transformation of education, namely with skills and entrepreneurial training that will create a generation into an entrepreneur. .This type of research is qualitative descriptive field research. The technique in determining the research subjects that I use is the sampling technique aimed at (purposive sampling). The techniques for collecting data are through observation, interviews and documentation. Data analysis techniques with reduction, display, and verification. Whereas to test the credibility of the data the author uses triangulation techniques.The results of the study show that career guidance in fostering entrepreneurial behavior of santri at the Ad-Dhuha Bantul Yogyakarta entrepreneurial boarding school is as follows: First. Implementation of career guidance is implemented through a plan, implementation (basic services, responsive services, individual planning, system support) and evaluation. Second. The impact of career guidance in shaping student behavior has had a positive impact in terms of cognitive, affective and psychomotor. Students have values of responsibility, honesty, discipline, independence, hard work, confidence, initiative, and energy. Third. As for the supporting factors and inhibitors of career guidance in fostering entrepreneurial behavior of the santri including Supporting factors consisting of pesantren founders are successful entrepreneurs of Bantul, boarding schools have their own internships, the geographical location of pesantren is quite safe and comfortable. The inhibiting factor consists of Islamic boarding schools that do not yet have the concept of structured entrepreneurship education, inadequate teaching staff, the absence of ICT laboratories, the minimal time available, and the age of students who are not uniform.